Impact of temperature and nutrient dynamics on growth and survival of Corbicula fluminea: A field study in oligotrophic Lake Constance. Issue 1 (10th March 2017) - Basen, Timo; Fleckenstein, Katja M.; Rinke, Karsten; Rothhaupt, Karl‐Otto; Martin‐Creuzburg, Dominik
Abstract : The invasive clam Corbicula fluminea was first recorded in Lake Constance (Germany) in 2003 and subsequently established high population densities at various locations in the lake. In 2010, four standardized field experiments were conducted in Lake Constance, one in each season, to investigate seasonal changes in somatic growth and survival of C. fluminea at different water depths. Somatic growth and survival of the clams were related to seasonal variations in water temperature and seston characteristics, that is, phytoplankton species composition and essential nutrient concentrations, and to the elemental and biochemical composition of clam tissues using principal component analyses and regression models. The field experiments revealed that somatic growth and survival of C. fluminea in Lake Constance were primarily determined by water temperature. In winter, low temperatures (<5°C) and low food supply resulted in high mortality and zero growth. Positive somatic growth rates were recorded in the lake throughout the growing season, when the water temperatures exceeded 10°C. Other seston variables, that is, particulate organic carbon content, phytoplankton species composition, and the elemental (nitrogen, phosphorus) and biochemical (fatty acids, sterols) nutrient composition were of minor importance for growth and survival of C. fluminea in oligotrophic Lake Constance. In parallel to the field experiments, standardized laboratory growth experiments were conducted to assess the effects of temperature on clam growth and survival at high food quantity and quality. The results from the laboratory experiments confirmed the conclusion that somatic growth and survival of C. fluminea in Lake Constance were primarily determined by water temperature. Our data suggest that further spread of C. fluminea may be supported by climate change, because milder winter temperatures and an earlier onset of thermal stratification in spring may reduce winter mortality and thereby extend the growing season for C. fluminea .